From Shulhoyf to Montparnasse: Cultural Collage in Moshé Vorobeichic’s Photography Book The Ghetto Lane in Wilna (1931) - Kvietkauskas, Mindaugas (Colloquia, 2021)
This article discusses the artistic genesis of the first avantgarde photography book in Lithuanian art history, The Ghetto Lane in Wilna (1931) by Moshé Vorobeichic-Moï Ver (Moshe Raviv, 1904–1995), and aims to conduct the first in-depth reconstruction of Vorobeichic’s early biographical and creative period in Vilnius in the 1920s in the local Jewish and multicultural milieu. The research is based on archival materials from Lithuanian state archives and the Raviv family archives in Israel. Vorobeichic, who was born in 1904 in Zaskavichy (currently in Belarus), made his artistic debut in Vilnius in 1923, and studied at the Faculty of Fine Art at Stephen Bathory University from 1923 to 1925. He continued his art studies at the Bauhaus school in Dessau (1927 to 1929) and, from 1929 in Paris at the École Technique de Photographie et de Cinématographie. From 1930 onwards, the photographer used the artistic pseudonym Moï Ver, under which his avant-garde photography book Paris, hailed as a masterpiece of the genre, was published by Editions Jeanne Walter in 1931. During the same period, Vorobeichic participated in Jewish cultural life in Vilnius, and was involved in the early stages of the formation of Yung Vilne, the acclaimed literary and artistic group of interwar Yiddish Modernism. The article aims to identify the cultural contexts in which Moï Ver’s artistic world-view and avant-garde style started to develop. The reconstruction of these contexts makes it possible to identify new semantic aspects in his avant-garde photography book The Ghetto Lane in Wilna, and to rethink its artistic concept. In this way, the cross-cultural semantics of Moï Ver’s photographic collages of Jewish Vilnius will emerge.